P61 Transcriptomic analysis of endothelium from human hepatocellular carcinoma highlights its potential to suppress anti-tumour immune responses. (28th September 2020) - O'Rourke, Joanne; Patten, Daniel; Wilkinson, Alex; Cain, Owen; Bicknell, Roy; Shetty, Shishir
Abstract : Promising outcomes with recent immune checkpoint inhibitor trials in hepatocellular carcinoma (HCC) have encouraged the search for novel immunotherapies. The tumour microenvironment in hepatocellular carcinoma (HCC) is highly complex but aggressive tumours are characterised by the accumulation of immunosuppressive cell populations. The endothelium is described as the gatekeeper for immunity, however, the regulation of immune cell/endothelial interaction within HCC is poorly characterised. We aimed to increase our understanding of the biological processes taking place at the level of the tumour endothelium in HCC through RNA sequencing of the endothelium in isolation, comparing this to non-tumour endothelium. In addition, we further studied the tumour microenvironment by spatial transcriptomic analysis of whole HCC tissue sections. Methods: We undertook a validated technique for endothelial isolation using magnetic beads conjugated to Ulex agglutinin I, a lectin isolated from Ulex europaeus which binds specifically to the L-fucose residues present within glycoproteins on the surface of human endothelial cells. These beads were incubated with a single cell suspension of HCC tissue or distal non-tumour tissue. RNA was extracted and mRNA sequencing performed. We next analysed paraffin sections of resected HCCs with Nanostring® Digital Spatial Profiling (DSP) to provide further information on the localisation of immune signatures within the tumour microenvironment. Results: 5 paired tumour and distal non-tumour samples taken from patients who underwent surgical resection were analysed. 45 genes were identified as being significantly differentially expressed between the tumour and non-tumour endothelium (adjusted p value <0.05). 41 genes were upregulated in the tumour endothelium and 4 downregulated. Pathway analysis revealed 83 pathways that were down regulated (adjusted p value <0.05) and these were further grouped into 7 key clusters. Remarkably, these clusters were all related to immune related pathways: leucocyte mediated immunity; leucocyte mediated toxicity; leucocyte proliferation; cell killing; exocytosis; cytokine production and cellular response to cytokine stimulus. DSP analysis provided additional spatial transcriptomic data, highlighting differential inflammatory signature expression between the tumour and tumour capsule. Conclusion: Our results demonstrate that the phenotype of tumour endothelium contributes to pathways which promote immune privilege in HCC. Spatial transcriptomics can provide further insight of how endothelial profiling correlates with immune cell infiltration in HCC. We have identified several new genes which need further validation but could be novel therapeutic targets that reprogramme the tumour endothelium and boost the efficacy of current immunotherapies.